Improving English vocabulary learning for students of Medical English at a medical college in Hanoi through games: An action research project - Nguyễn, Thị Oanh (2020)
One of the most challenging tasks facing any language teachers is to capture students’interest, and therefore, keep them in high learning spirit. Meanwhile, vocabulary learning is a hard task which can sometimes be frustrating especially for teenagers. To realize this situation, the teachers are supposed to find out teaching approaches corresponsive to students’ needs and wants. The study, in that light, lays a focus on students’ improvement in learning medical English vocabulary through language games. The study is conductedin the form of an action research with the research tools being teacher’s diary, pre-test, post-test and survey questionnaire to collect data. Then the data from teacher’s diary and tests were exploited to find out the improvement in students’ vocabulary. And the data from survey questionnaire were used to find out students’ attitudes towards language games and provide factors that should be considered by teachers when using games to teach medical English vocabulary. Through the results of the teacher’s diary, the pre-test and post-test, it can be concluded that language games could help improve students' vocabulary retention. The results collected from the questionnaires showed that most of the students expressed their positive attitudes towards the games carried out in teaching medical vocabulary.